Preparation process of high-strength high-toughness wear-resistant titanium alloy composite material
By preheating the titanium alloy, three-stage solid solution and pre-aging treatment, and using laser cladding wear-resistant composite materials after the surface is sandblasted, the problem of poor wear resistance of titanium alloy is solved, and high-strength, high-strength, high-strength, wear-resistant composite is achieved The preparation of materials improves the bonding performance of the coating and the matrix and the comprehensive performance of the material.
Patent Information
- Application Number
- CN202411436529.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
Titanium alloy has poor wear resistance in its application, which leads to the wear-resistant coating being easily shedded and the surface being easily cracked, limiting its application in the aerospace, marine industry and automobile industry.
By preheating the titanium alloy, three-stage solid solution and pre-aging treatment, uniform and fine isometric crystals are formed to reduce the surface lubricity, and the wear-resistant composite materials are clad with laser cladding technology after the surface sandblasting treatment to enhance The bonding properties of the coating and the substrate.
It significantly improves the bonding performance between wear-resistant coating and titanium alloy, extends the protective aging of the coating, improves the toughness and wear resistance of titanium alloy composite materials, and expands its applicable fields, especially in aerospace and automobiles. industry.
Smart Images

Figure CN119320921A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy composite material preparation, and relates to a preparation process of a high-strength, high-toughness, and wear-resistant titanium alloy composite material. Background Art
[0002] Titanium alloys are widely used in aerospace, marine, automotive and other fields due to their high strength, high toughness and good corrosion resistance. However, titanium alloys themselves have the disadvantage of poor wear resistance, which limits their application.
[0003] Usually, the wear resistance of titanium alloy is improved by applying composite wear-resistant coating on the surface of titanium alloy. The bonding performance between wear-resistant coating and titanium alloy is one of the important factors affecting the improvement of wear resistance of titanium alloy by wear-resistant coating. The better the bonding performance between wear-resistant coating and titanium alloy, the longer the protective effect of wear-resistant coating on titanium alloy, the better the protective effect, and the better the improvement effect of wear-resistant coating on the performance of titanium alloy. The emergence of laser cladding technology provides a good foundation for modifying the surface performance of titanium alloy. However, when wear-resistant coating is clad on the surface of titanium alloy by laser cladding technology, the wear-resistant coating is still easy to fall off and the surface is easy to crack, which limits the improvement effect of wear-resistant coating on the performance of titanium alloy.
[0004] Therefore, it is necessary to provide a preparation process for high-strength, high-toughness, and wear-resistant titanium alloy composite materials, effectively enhance the bonding performance between the wear-resistant coating clad by laser cladding technology and the titanium alloy substrate, and improve the improvement effect of the wear-resistant coating on the titanium alloy, so as to finally prepare a high-strength, high-toughness, and wear-resistant titanium alloy composite material with a long protection time and good protection effect. Summary of the invention
[0005] In order to overcome the problems in the background technology, the present invention performs pretreatments such as preheating, three-stage solid solution, and pre-aging treatment on the titanium alloy before laser cladding, so as to form uniform and fine equiaxed crystals in the titanium alloy, and at the same time, the precipitated phase and the matrix in the titanium alloy are tightly combined, thereby reducing the surface lubricity of the titanium alloy, thereby improving the bonding performance between the wear-resistant coating and the titanium alloy, and realizing long-term and effective protection of the wear-resistant coating on the titanium alloy.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] The preparation process comprises the following steps:
[0008] (1) Preheating the titanium alloy;
[0009] (2) performing a three-stage solid solution treatment on the titanium alloy after the preheat treatment in step (1), and then water quenching the titanium alloy to obtain a quenched titanium alloy sample;
[0010] (3) performing a pre-aging treatment on the quenched titanium alloy sample obtained in step (2), and then air-cooling the titanium alloy to room temperature;
[0011] (4) performing surface sandblasting on the titanium alloy after cooling in step (3) to obtain a titanium alloy substrate;
[0012] (5) using laser cladding technology to clad a layer of wear-resistant composite material on the surface of the titanium alloy substrate obtained in step (4);
[0013] (6) performing an aging treatment on the titanium alloy coated with the wear-resistant composite material in step (5), and then air-cooling the titanium alloy coated with the wear-resistant composite material to room temperature to obtain a titanium alloy composite material.
[0014] Preferably, in step (1), the preheating temperature is 200° C. and the preheating time is 1 hour.
[0015] Preferably, in step (2), the first stage solution treatment is carried out at 850°C for 2 hours, then the second stage solution treatment is carried out at 900°C for 2 hours, and finally the third stage solution treatment is carried out at 950°C for 2 hours.
[0016] Preferably, in step (3), the pre-aging treatment temperature is 450° C. and the pre-aging treatment time is 2 h.
[0017] Preferably, in step (5), the wear-resistant composite material is composed of zirconia toughened alumina ceramic particles, high chromium cast iron powder, and an adhesive. The wear-resistant composite material comprises, by mass fraction, 20% zirconia toughened alumina ceramic particles, 75% high chromium cast iron powder, and 5% adhesive.
[0018] Preferably, in step (5), the laser power during the laser cladding process is 6-8 kW, the cladding speed is 700-900 mm / min, and a 50% overlap rate is used to complete the cladding of the entire wear-resistant composite material.
[0019] Preferably, in step (6), the aging treatment temperature is 400-420° C., and the holding time is 4 hours.
[0020] Preferably, the titanium alloy is TC4, and its composition by mass fraction is: Al: 5.5%-6.75%, V: 3.5%-4.5%, and the remainder is Ti and impurity elements.
[0021] Beneficial effects of the present invention:
[0022] 1. The present invention forms a mutual complement and optimization effect on the titanium alloy through preheat treatment, three-stage solution treatment and pre-aging treatment, which jointly affect the microstructure and macroscopic properties of the material, thereby improving the bonding performance between the precipitated phase and the matrix in the titanium alloy, reducing the surface lubricity of the titanium alloy, so as to enhance the bonding performance between the corrosion-resistant coating and the titanium alloy, and realize the long-term and effective protection of the wear-resistant coating on the titanium alloy.
[0023] 2. The present invention gradually releases the internal stress of the material through three-stage solid solution treatment, reduces the risk of deformation and cracking during processing, and at the same time, gradually increases the atomic solubility, makes the solute atoms dissolve more evenly, forms a supersaturated solid solution, and makes the precipitated phase in the titanium alloy fine and uniform, which helps to improve the toughness of the titanium alloy itself, so that the final titanium alloy composite material has higher toughness.
[0024] 3. The present invention forms a wear-resistant composite material composed of zirconium oxide toughened alumina ceramic particles, high chromium cast iron powder and adhesive by cladding on the surface of titanium alloy. Due to the mutual diffusion and chemical reaction of elements at the interfaces of the components of the wear-resistant composite material, it not only provides metallurgical bonding, but also enhances the interface bonding strength through mechanical bonding and chemical reaction to form a dense and continuous transition layer. Therefore, the wear-resistant composite material not only has excellent wear resistance, but also has high strength, which helps to improve the wear resistance and strength of the final titanium alloy composite material.
[0025] 4. The present invention performs sandblasting on the titanium alloy surface before laser cladding the wear-resistant coating, thereby achieving the purpose of cleaning the titanium alloy surface and increasing the surface roughness of the titanium alloy, while refining the grains of the titanium alloy surface layer to form a nanocrystalline structure, thereby further improving the bonding performance between the wear-resistant coating and the titanium alloy substrate.
[0026] 5. The wear-resistant coating clad on the surface of the titanium alloy by laser cladding technology in the present invention has no defects such as cracks and pores. At the same time, the wear-resistant coating has excellent bonding performance with the titanium alloy matrix, which can form effective and long-term protection for the titanium alloy, so that the titanium alloy composite material prepared by the present invention has higher toughness, strength and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific embodiments.
[0029] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.
[0030] Example 1
[0031] In this embodiment, a titanium alloy composite material is prepared by the following steps:
[0032] (1) Cut the TC4 bar into square bar specimens with the dimensions of 30 mm × 30 mm × 10 mm in length, width and height respectively;
[0033] (2) Preheat the cut samples at 200°C for 1 hour.
[0034] (3) The preheated square rod specimens were subjected to three-stage solution treatment: the first stage solution temperature was 850°C and the holding time was 2 h; the second stage solution temperature was 900°C and the holding time was 2 h; the third stage solution temperature was 950°C and the holding time was 2 h. After that, the specimens were quenched by water cooling for 5 min.
[0035] (4) The square rod specimens after solution treatment were subjected to pre-aging treatment at a holding temperature of 450 °C for 2 h, and then air-cooled to room temperature.
[0036] (5) The surface of the square rod-shaped specimen after pre-aging treatment was sandblasted using steel shots with a size of 0.5 to 1.0 mm. The sandblasting pressure was set to 2.6 MPa and the sandblasting time was 12 min.
[0037] (6) The wear-resistant composite material is clad on the surface of the square rod-shaped specimen after sandblasting by using laser cladding technology. The laser power is 6kW, the cladding speed is 700mm / min, and the cladding of all the wear-resistant composite materials is completed by using a 50% overlap rate. Before laser cladding, the raw materials required for laser cladding are prepared. The specific production process of the raw materials used for laser cladding is as follows: zirconia toughened alumina ceramic particles (ZTA), high chromium cast iron powder (HCCI), and adhesive are mixed according to the mass fraction of 20% zirconia toughened alumina ceramic particles, 75% high chromium cast iron powder, and 5% adhesive (water glass is used as the adhesive). The mixture is stirred evenly and placed in a mold for sintering to form a preform, which can be used as a laser cladding raw material.
[0038] (7) The square rod-shaped specimen after the wear-resistant coating was clad was subjected to aging treatment at a temperature of 400°C for 4 h, and then air-cooled to room temperature to obtain a high-strength, high-toughness, and wear-resistant titanium alloy composite material.
[0039] The titanium alloy composite material prepared in this embodiment has a surface wear-resistant coating without cracks. When the titanium alloy composite material prepared in this embodiment is lightly tapped with a tapping tool, no obvious debris peeling or cracking occurs, showing excellent adhesion performance. After the mechanical friction test, the wear-resistant layer remains stable and intact without falling off or peeling.
[0040] Example 2
[0041] In this embodiment, a titanium alloy composite material is prepared by the following steps:
[0042] (1) Cut the TC4 bar into square bar specimens with the dimensions of 30 mm × 30 mm × 10 mm in length, width and height respectively;
[0043] (2) Preheat the cut samples at 200°C for 1 hour.
[0044] (3) The preheated square rod specimens were subjected to three-stage solution treatment: the first stage solution temperature was 850°C and the holding time was 2 h; the second stage solution temperature was 900°C and the holding time was 2 h; the third stage solution temperature was 950°C and the holding time was 2 h. After that, the specimens were quenched by water cooling for 5 min.
[0045] (4) The square rod specimens after solution treatment were subjected to pre-aging treatment at a holding temperature of 450 °C for 2 h, and then air-cooled to room temperature.
[0046] (5) The surface of the square rod-shaped specimen after pre-aging treatment was sandblasted using steel shots with a size of 0.5 to 1.0 mm. The sandblasting pressure was set to 2.8 MPa and the sandblasting time was 11 min.
[0047] (6) The wear-resistant composite material was clad on the surface of the square rod-shaped specimen after sandblasting using laser cladding technology. The laser power was 7 kW, the cladding speed was 800 mm / min, and a 50% overlap rate was used to complete the cladding of the entire wear-resistant composite material.
[0048] (7) The square rod-shaped specimen after the wear-resistant coating was clad was subjected to aging treatment at a temperature of 410°C for 4 h, and then air-cooled to room temperature to obtain a high-strength, high-toughness, and wear-resistant titanium alloy composite material.
[0049] The titanium alloy composite material prepared in this embodiment has a surface wear-resistant coating without cracks. When the titanium alloy composite material prepared in this embodiment is lightly tapped with a tapping tool, no obvious debris peeling or cracking occurs, showing excellent adhesion performance. After the mechanical friction test, the wear-resistant layer remains stable and intact without falling off or peeling.
[0050] Example 3
[0051] In this embodiment, a titanium alloy composite material is prepared by the following steps:
[0052] (1) Cut the TC4 bar into square bar specimens with the dimensions of 30 mm × 30 mm × 10 mm in length, width and height respectively;
[0053] (2) Preheat the cut samples at 200°C for 1 hour.
[0054] (3) The preheated square rod specimens were subjected to three-stage solution treatment: the first stage solution temperature was 850°C and the holding time was 2 h; the second stage solution temperature was 900°C and the holding time was 2 h; the third stage solution temperature was 950°C and the holding time was 2 h. After that, the specimens were quenched by water cooling for 5 min.
[0055] (4) The square rod specimens after solution treatment were subjected to pre-aging treatment at a holding temperature of 450 °C for 2 h, and then air-cooled to room temperature.
[0056] (5) The surface of the square rod-shaped specimen after pre-aging treatment was sandblasted using steel shots with a size of 0.5 to 1.0 mm. The sandblasting pressure was set to 3.0 MPa and the sandblasting time was 10 min.
[0057] (6) The wear-resistant composite material was clad on the surface of the square rod-shaped specimen after sandblasting using laser cladding technology. The laser power was 8 kW, the cladding speed was 900 mm / min, and a 50% overlap rate was used to complete the cladding of the entire wear-resistant composite material.
[0058] (7) The square rod-shaped specimen after the wear-resistant coating was clad was subjected to aging treatment at a temperature of 420°C for 4 h, and then air-cooled to room temperature to obtain a high-strength, high-toughness, and wear-resistant titanium alloy composite material.
[0059] The titanium alloy composite material prepared in this embodiment has a surface wear-resistant coating without cracks. When the titanium alloy composite material prepared in this embodiment is lightly tapped with a tapping tool, no obvious debris peeling or cracking occurs, showing excellent adhesion performance. After the mechanical friction test, the wear-resistant layer remains stable and intact without falling off or peeling.
[0060] Comparative Example 1
[0061] The titanium alloy composite material was prepared in this comparative example by the same method as in Example 1, except that: no preheating treatment was performed in this comparative example, and the cut square rod-shaped specimens were directly subjected to a three-stage solution treatment.
[0062] The titanium alloy composite material prepared in this comparative example was lightly tapped with a tapping tool, and no obvious cracks appeared, but there was slight chip peeling. Since the titanium alloy was not preheated, the initial microstructure of the solute atoms was uneven, which had a negative impact on the subsequent solution treatment. Preheat treatment can improve the plasticity and toughness of the material, create a more uniform initial microstructure for solution treatment, and enable the alloy elements to be more evenly dissolved in the matrix during solution treatment.
[0063] Comparative Example 2
[0064] The titanium alloy composite material was prepared in the present comparative example by the same method as in Example 1, except that: the present comparative example did not perform the three-stage solution treatment, but directly performed the solution treatment for 6 h on the preheated square rod-shaped specimen at 950°C.
[0065] The titanium alloy composite material prepared in this comparative example was tapped lightly with a tapping tool, and no debris peeling occurred, but the tapping sound changed and became crisper. This is because direct solution treatment at 950°C will cause the material to produce greater internal stress. Multi-stage solution treatment can gradually release the stress inside the material, reduce the risk of deformation and cracking during processing, and more effectively dissolve the strengthening phase in the alloy, reduce microsegregation, and thus obtain a more uniform microstructure.
[0066] Comparative Example 3
[0067] The titanium alloy composite material was prepared in this comparative example by the same method as in Example 1, except that: the pre-aging treatment was not performed in this comparative example, and the sample was directly sandblasted after the three-stage solution treatment.
[0068] The titanium alloy composite material prepared in this comparative example was lightly tapped with a tapping tool, and obvious debris peeling occurred. The surface activity of the workpiece without pre-aging treatment is insufficient, resulting in reduced adhesion of the cladding layer after sandblasting, affecting the durability and protective effect of the cladding layer. Therefore, the process step of pre-aging treatment cannot be ignored.
[0069] Comparative Example 4
[0070] The titanium alloy composite material is prepared in this comparative example by the same method as in Example 1, except that the wear-resistant material in this comparative example is HCCI, and is not composited with ZTA.
[0071] By comparing with Example 1, it is found that under the same mechanical wear conditions, the wear amount of the titanium alloy composite material in this comparative example is three times that of Example 1. Under actual working conditions, the wear resistance of the ZTA / HCCI composite material is four times higher than that of HCCI. This shows that the ZTA / HCCI composite material has excellent wear resistance compared with single-element wear-resistant materials.
[0072] Comparative Example 5
[0073] The titanium alloy composite material was prepared in this comparative example by the same method as in Example 1, except that: in this comparative example, no aging treatment was performed after the wear-resistant composite material was clad.
[0074] The titanium alloy composite material prepared in this comparative example was tapped lightly using a tapping tool under the same tapping force as in Example 1, and slight cracks appeared on the surface of the titanium alloy composite material. Since this comparative example did not undergo the final aging treatment, large internal stress existed on the surface of the wear-resistant coating, increasing its cracking risk.
[0075] Table 1
[0076]
[0077] It can be seen from Table 1 that the titanium alloy composite material prepared by the present invention has high strength and toughness, and excellent wear resistance. In addition, in the titanium alloy composite material prepared by the present invention, the density, uniformity and stability of the wear-resistant coating are all at a high level, and the bonding strength between the wear-resistant coating and the titanium alloy substrate is high, and the bonding performance is good.
[0078] In summary, the titanium alloy composite material prepared by the present invention exhibits excellent comprehensive properties. At the same time, in the titanium alloy composite material of the present invention, the wear-resistant coating and the titanium alloy matrix have excellent bonding performance, which can protect the titanium alloy composite material for a long time and expand the application field of titanium alloy, especially in the aerospace and automotive industries.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A preparation process of a high-strength, high-toughness, wear-resistant titanium alloy composite material, characterized by: The preparation process comprises the following steps: (1) Preheating the titanium alloy; (2) performing a three-stage solid solution treatment on the titanium alloy after the preheat treatment in step (1), and then water quenching the titanium alloy to obtain a quenched titanium alloy sample; (3) performing a pre-aging treatment on the quenched titanium alloy sample obtained in step (2), and then air-cooling the titanium alloy to room temperature; (4) performing surface sandblasting on the titanium alloy after cooling in step (3) to obtain a titanium alloy substrate; (5) using laser cladding technology to clad a layer of wear-resistant composite material on the surface of the titanium alloy substrate obtained in step (4); (6) performing an aging treatment on the titanium alloy coated with the wear-resistant composite material in step (5), and then air-cooling the titanium alloy coated with the wear-resistant composite material to room temperature to obtain a titanium alloy composite material.
2. The process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (1), the preheating temperature is 200° C. and the preheating time is 1 hour.
3. The preparation process of a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (2), the first stage solution treatment is carried out at 850°C for 2 hours, then the second stage solution treatment is carried out at 900°C for 2 hours, and finally the third stage solution treatment is carried out at 950°C for 2 hours.
4. The process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (3), the pre-aging treatment temperature is 450° C. and the pre-aging treatment time is 2 h.
5. The process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (5), the wear-resistant composite material is composed of zirconium oxide toughened alumina ceramic particles, high chromium cast iron powder, and adhesive. The wear-resistant composite material includes, by mass fraction: 20% of zirconium oxide toughened alumina ceramic particles, 75% of high chromium cast iron powder, and 5% of adhesive.
6. The process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (5), the laser power during the laser cladding process is 6-8 kW, the cladding speed is 700-900 mm / min, and a 50% overlap rate is used to complete the cladding of the entire wear-resistant composite material.
7. The process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to claim 1, characterized in that: In the step (6), the aging treatment temperature is 400-420° C., and the insulation time is 4 hours.
8. A process for preparing a high-strength, high-toughness, wear-resistant titanium alloy composite material according to any one of claims 1 to 7, characterized in that: The titanium alloy is TC4, and its composition by mass fraction is: Al: 5.5%-6.75%, V: 3.5%-4.5%, and the remainder is Ti and impurity elements.